Introduction to electromagnetic theory : a modern perspective - Chow, Tai L. (Jones and Bartlett, 2006)
Introduction to Electromagnetic Theory presents a complete account of classical electromagnetism with a modern perspective. Its focused approach delivers numerous problems of varying degrees of difficulty for continued study. The text gives special attention to concepts that are important for the development of modern physics, and also discusses applications to other areas of physics wherever possible. A generous amount of detail has been in given in mathematical manipulations and vectors are employed right from the start.